Mechanical, thermal and morphological properties of epoxy resin toughened with epoxidized soybean oil - Abu Bakar, M.B; Masri, M.N; Mohamad Amini, M.H; Mohd Thirmizir, M.Z; Salim, M.S (2018)
Biobased toughened thermosetting polymer blend was prepared by incorporating epoxidized soybean oil (ESO) into a petroleum-based epoxy (DGEBA) in different composition ratios. The mechanical properties (tensile and flexural tests) of the ESO/DGEBA thermoset blends were determined. Thermal properties of the blends were characterized using thermogravimetric analysis. The result showed that, the tensile and flexural properties decreased with increasing of ESO content. However, a slight increase in the strength properties was observed at 10% of ESO content. A significant enhancement in impact strength proves the role of ESO acting as a plasticizer in the blends as well as improve the toughness properties of ESO/DGEBA thermoset blend. As the ESO content increase, the thermal stability of ESO/DGEBA thermoset blend has decreased might be due to reduced cross-linking density of the epoxy network. Further investigations on morphological properties were also done to correlate the mechanical properties of ESO/DGEBA thermoset blend.